Different types of resistance training in type 2 diabetes mellitus: effects on glycaemic control, muscle mass and strength - Andreas Egger; David Niederseer; Gernot Diem; Thomas Finkenzeller; Eveline Ledl-Kurkowski; Rosemarie Forstner; Christian Pirich; Wolfgang Patsch; Raimund Weitgasser; Josef Niebauer (2012)
Resistance training has become a mainstay of exercise training in type 2 diabetes mellitus (T2DM). However, it remains controversial whether hypertrophy resistance training (HRT) is superior to endurance resistance training (ERT) with regard to its effects on glycaemic control, muscle mass and strength. Thirty-two patients with T2DM (13 men and 19 women; 64.8 ± 7.8 years) were randomly assigned to either eight weeks of HRT (n = 16; 2 sets, 10–12 repetitions, 70% of the one-repetition maximum (1-RM)) or ERT (n = 16; 2 sets, 25–30 repetitions, 40% 1-RM). In addition, all patients participated in aerobic exercise training (AET; 1 hour/day on 2 non-consecutive days/week; cycle ergometer; 70% of heart rate reserve). After eight weeks of intervention, there were time but not group effects for reduced glucose and fructosamine levels, weight, BMI, waist circumference, subcutaneous abdominal fat, resting heart rate, systolic and diastolic blood pressure; muscle mass of the arms and physical exercise capacity increased significantly. Significant time and group effects were documented for maximum strength of the chest, with a greater increase for HRT than ERT (p = 0.01). Specific maximal resistance training of the chest muscles led to superior gain in strength as compared to endurance resistance training. This, however, did not translate into superior values of glycaemic control, weight, waist circumference, muscle mass and physical work capacity, which all improved significantly by a similar magnitude in both groups. Since overall effects of both protocols were comparable, both may be offered to patients according to their personal preference.